Обобщенные представления субгаpмонических функций в полуплоскости - Малютин, К.Г.; Герасименко, В.А. (Видавничий дім "Академперіодика" НАН України, 2007)
We obtain the presentation of subharmonic functions of finite gamma-growth in a half-plane. This presentation is a generalization of the known integral formulas for the subharmonic functions of finite order.